Iklan dan Penggunaan Model Anak-Anak - Watie, Errika Dwi Setya (Jurnal The Messenger, 2013)
There are many studies that prove how much influences ads on the audience, unfortunately there are many ads that it still violates Etika Pariwara Indonesia that has been determined. In the framework developed Lavidge and Steiner (1961) demonstrated the influence of the flow of mass communication. The framework has six steps from viewing the media audience to how does audience media act. Many ads using children as models of the ad. This is certainly allowed, but still have to pay attention to ethics-related, that in accordance with the view that there should be display ads in Indonesia.